Achieving Efficient Phosphorescence and Mechanoluminescence in Organic Host–Guest System by Energy Transfer. (23rd September 2021) - Yang, Jianhui; Wu, Xinghui; Shi, Jianbing; Tong, Bin; Lei, Yunxiang; Cai, Zhengxu; Dong, Yuping
Abstract: Host–guest doping strategy greatly facilitates and expands the scope of construction of organic phosphorescence materials. Herein, triphenylamine with excellent crystallinity is chosen as the host, and four guests with 2–4 triphenylamine repeating units are chosen as the guests. The similarity in molecular structures of the host and guests simplifies the exploration of the luminescence mechanism in the doped system. The doped materials display strong room temperature phosphorescence (RTP) with above 200 ms lifetimes and 30% quantum yields. In addition, the doped system emits blue fluorescence under mechanical stimulation, that is, shows a phenomenon of mechanoluminescence (ML). The experimental results prove that the host plays different roles in different luminescence processes. In the photophosphorescence process, the triplet energy level of the host assists the guest excitons to undergo intersystem crossing. Meanwhile, in the ML process, the energy generated as a result of piezoelectric property of the host crystal is transferred to the guest, causing the guest molecules to emit fluorescence. This work is significant for the construction of doped materials with multiple luminescence properties, including RTP and ML. Abstract : A series of host‐guest doping materials possessing both room temperature phosphorescence (RTP) and mechanoluminescence (ML) characteristics are developed. The luminescence mechanisms of both RTP and ML are well investigated. These materials are finely applied in data encryption and anti‐counterfeiting.